Structural and Functional Diversity of Plant Virus 3′-Cap-Independent Translation Enhancers (3′-CITEs) - Truniger, Verónica; Miras, Manuel; Aranda, Miguel A. (Frontiers in Plant Science, 2017)
Most of the positive-strand RNA plant viruses lack the 5′-cap and/or the poly(A)-tail that act synergistically to stimulate canonical translation of cellular mRNAs. However, they have RNA elements in the 5′- or 3′-untranslated regions of their RNAs that are required for their cap-independent translation. Cap-independent translation enhancers (CITEs) have been identified in the genomic 3′-end of viruses belonging to the family Tombusviridae and the genus Luteovirus. Seven classes of 3′-CITEs have been described to date based on their different RNA structures. They generally control the efficient formation of the translation initiation complex by varying mechanisms. Some 3′-CITEs bind eukaryotic translation initiation factors, others ribosomal subunits, bridging these to the 5′-end by different mechanisms, often long-distance RNA–RNA interactions. As previously proposed and recently found in one case in nature, 3′-CITEs are functionally independent elements that are transferable through recombination between viral genomes, leading to potential advantages for virus multiplication. In this review, the knowledge on 3′-CITEs and their functioning is updated. We also suggest that there is local structural conservation in the regions interacting with eIF4E of 3′-CITEs belonging to different classes.